Potential of unmanned aerial vehicle-based remote sensing to detect water stress and estimate yield in pecan - Taylor, Nicolette Jane (University of Pretoria, 2023)
Dissertation (MSc (Agric) Horticulture)--University of Pretoria, 2023.